Achieving the Optimal Epinephrine Effect in Wide Awake Hand Surgery using Local Anesthesia without a Tourniquet. (December 2015) - Mckee, Daniel E.; Lalonde, Donald H.; Thoma, Achilleas; Dickson, Lisa
Background: In our experience, for all surgeries in the hand, the optimal epinephrine effect from local anesthesia—producing maximal vasoconstriction and visualization—is achieved by waiting significantly longer than the traditionally quoted 7 min from the time of injection. Methods: In this prospective comparative study, healthy patients undergoing unilateral carpal tunnel surgery waited either 7 min or roughly 30 min, between the time of injection of 1 % lidocaine with 1:100, 000 epinephrine and the time of incision. A standardized incision was made through dermis and into the subcutaneous tissue followed by exactly 60 s of measuring the quantity of blood loss using sterile micropipettes. Results: There was a statistically significant reduction in the mean quantity of bleeding in the group that waited roughly 30 min after injection and before incision compared to the group that waited only 7 min (95 % confidence intervals of 0.06+–0.03 ml/cm of incision, compared to 0.17+–0.08 ml/cm, respectively) (P=0.03). Conclusions: Waiting roughly 30 min after injection of local anesthesia with epinephrine as oppose to the traditionally taught 7 min, achieves an optimal epinephrine effect and vasoconstriction. In the hand, this will result in roughly a threefold reduction in bleeding—making wide awake local anesthesia without tourniquet (WALANT) possible. This knowledge has allowed our team to expand the hand procedures that we can offer using WALANT. The benefits of WALANT hand surgery include reduced cost and waste, improved patient safety, and the ability to perform active intraoperative movement examinations.